Charge transfer to ground-state ions produces free electrons - D. You (Nature Portfolio, 2017)
Slow electrons, which cause radiation damage, are efficiently produced by interatomic neutralization processes. Here, the authors show experimental evidence for the efficient neutralization of the ionic states produced in Auger decay, using large neon–krypton clusters as a prototype system.